1990
DOI: 10.1007/bf00862530
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal angiotensinogen: localization and regulation

Abstract: Multiple lines of evidence (physiologic, immunohistochemical, and molecular biologic) support the presence of a complete intrarenal renin-angiotensin system (RAS). Localization of angiotensinogen messenger ribonucleic acid (mRNA) within the proximal tubule, together with demonstration of renin and converting enzyme mRNAs within the kidney, provide the most persuasive evidence for local, independent synthesis. Data from a combination of in situ hybridization studies, Northern analysis, and physiologic manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…26 As described, angiotensinogen mRNA levels appear stable during chronic diabetes, whereas angiotensinogen protein expression increased after 4 and 8 months and then decreased after 12 months of diabetes. This discrepancy between the lack of change in angiotensinogen gene expression and the fluctuation in angiotensinogen protein could be due to changes in translational efficiency, transcript degradation, or increased uptake of circulating angiotensinogen by the proximal tubule.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…26 As described, angiotensinogen mRNA levels appear stable during chronic diabetes, whereas angiotensinogen protein expression increased after 4 and 8 months and then decreased after 12 months of diabetes. This discrepancy between the lack of change in angiotensinogen gene expression and the fluctuation in angiotensinogen protein could be due to changes in translational efficiency, transcript degradation, or increased uptake of circulating angiotensinogen by the proximal tubule.…”
Section: Discussionmentioning
confidence: 63%
“…This discrepancy between the lack of change in angiotensinogen gene expression and the fluctuation in angiotensinogen protein could be due to changes in translational efficiency, transcript degradation, or increased uptake of circulating angiotensinogen by the proximal tubule. Previously, the presence of extrahepatic angiotensinogen gene transcripts in multiple organs has served as evidence for local renin-angiotensin systems, 27 and recently a tubular angiotensin generating system 26 was proposed. Whether the presence and alteration of angiotensinogen gene and protein expression in the diabetic kidney reflects an alteration in tubular function/ regulation is not known and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies in Wistar-Kyoto rats, it was demonstrated that 1) renal angiotensinogen mRNA levels in males increase significantly during puberty, 2) renal angiotensinogen mRNA levels in adult females are considerably lower than those in adult males, 3) renal an-giotensinogen mRNA levels in adult males are decreased by castration, and 4) renal angiotensinogen mRNA levels in adult females are increased by testosterone treatment. These data clearly indicated that androgen upregulates rat renal angiotensinogen mRNA expression (Ellison et al, 1989;Ingelfinger et al, 1990). In contrast to the renal angiotensinogen mRNA level, circulating angiotensinogen levels are higher in women than in men (Clauser et al, 1989).…”
Section: Renal Development and Agingmentioning
confidence: 73%
“…Nevertheless, although increased AGT mRNA is not obviously the same as increased AGT protein and AngII production, the published body of evidence indicates that AGT protein and AngII production is consensual to tissue mRNA levels both in kidney and adipose tissue. [12][13][14] Second, the new variants were more rare in the general population than in our patients, probably because of chance depending on the relatively small number of patients with kidney cancer that we were able to recruit. Third, these new variants should be tested in an appropriate human cell system to study AGT transcription rate, and also to exclude the eventuality that other linked variants were responsible for the effect.…”
Section: Discussionmentioning
confidence: 96%
“…13 In the kidney, a localized increase of AGT transcription may lead to an increased local AngII production with systemic effects due to the quantitative influence on tubular sodium re-absorption. Indeed, intrarenal AGT mRNA and protein have been localized mainly in proximal tubular cells, 14,15 and the high levels of intratubular and urinary AngII derive from locally synthesized AGT. Moreover, AngII plays an important role even in kidney medulla by the direct, aldosterone-independent regulation of the sodium epithelial channel in the collecting ducts, 14 a key final step in sodium and blood pressure control.…”
Section: Introductionmentioning
confidence: 99%